In Vitro Synergy of Levofloxacin Plus Piperacillin/Tazobactam against Pseudomonas aeruginosa - Vladimir Chachanidze; Aixa Curbelo-Irizarry; Deborah Ashcraft; George Pankey (Interdisciplinary Perspectives on Infectious Diseases)
In vitro synergy testing using levofloxacin (LVX) plus piperacillin/tazobactam (TZP) was performed by Etest and time-kill assay (TKA) for 31 unique fluoroquinolone-resistant Pseudomonas aeruginosa isolates. The Etest method showed synergy for 9/31 (29%) of isolates, while TKA showed synergy with 14/31 (45%) of isolates. When comparing the Etest method and TKA, concordant results for synergy, antagonism, and indifference were obtained for 24/31 (77%) of the isolates tested.